(untitled) (Theatrum historiae, 2011)
The study deals with the historiography reflection of the metamorphoses of the position of the Catholic church in Bohemia after 1918. I combine a basic overview of the development of the Czech and German Catholic milieu in the period between the wars with the reflection of these development trends in the Czech and, partially, German historiography while the core of the works depicted lies mainly in the last decade of the period. In order to depict circles of topics I deal mainly with phenomena which are related to the methods of the reflection of the post-war social and thought development of Catholic churches. Czechoslovakia was one of the examples of the religious development of Central and Western Europe, which was given by the influence of the secularisation affecting the public area as well as pronounced anti-Catholic sentiments. I also concentrate on issues concerning the relations between the confessional and national identity. In this period the Catholic church lived in a state of unceasing tension between modernisation and traditional conservative accents which were often reflected in the formation of the political culture in Czechoslovakia between the wars and in the Catholic attitude towards social issues. The study not only denominates the topics reflected, but also outlines the blind spots of the historiographic research as well as research impulses and other research trends.